Synthesis of new terpyridine-like ligands based on triazolopyridines and benzotriazoles. (23rd May 2017) - Cabrero-Antonino, M.; Ballesteros-Garrido, R.; Chiassai, L.; Escrivà, E.; Ramirez de Arellano, C.; Ballesteros, R.; Abarca, B.
Abstract : Herein, terpyridine triazole-based analogs bearing benzotriazoles or/and triazolopyridines are prepared via copper catalysis, where the arrangement of the nitrogen atoms is proven to be crucial to the spectroscopic properties of these ligands. Abstract : Herein, terpyridine triazole-based analogs bearing benzotriazoles or/and triazolopyridines are prepared via copper catalysis, where the arrangement of the nitrogen atoms is proven to be crucial to the spectroscopic properties of these ligands.